Kajian Kelayakan Finansial Alat Pengusir Burung Tanaman Padi Berbasis Sinar Laser - Hyacintha Dinda Septiana Putri; I Wayan Widia; I Gusti Ketut Arya Arthawan (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2024)
Bird s attack of rice plants can cause losses for farmers by reducing rice production. To overcome this problem, a laser light - based rice bird repelle r was developed. This repeller consists of a laser transmitter unit , frame unit , control and remote - control unit , and ener gy generator unit designed into one so that it can function as expected. Technically, this repeller can potentially reduce damage from bird s attack , but more information is needed regarding its financial feasibility. Th is study aimed to assess the economic feasibility of a laser - based rice bird repelle r . The data used in this study include investment costs, fixed costs, operational costs, reduction of losses, reduction of labor, residual value, and depreciation value. The assumptions applied in this study are that the a nnual fixed costs are the same throughout the analysis period, the economic life is five years, and the analysis interest rate is 6% /year. There are four criteria used to assess financial feasibility, namely Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Benefit Cost Ratio (BCR). The results show that the laser - based bird repelle r can be declared financially feasible, as indicated by an NPV value of IDR 10.381.941,88 , an IRR value of 23,91%, a Payback Period of 2,83 years and a BCR of 1 , 21 . Based on the sensitivity analysis results, it shows that this repeller remains financially not fe asible under economic conditions of declining revenue and simultaneous increases in expenses by 10%, 20%, and 30% annually , and it indicates that changes in interest rates have the most significant impact on the NPV value